Neuroprotective Roles of l-Cysteine in Attenuating Early Brain Injury and Improving Synaptic Density via the CBS/H2S Pathway Following Subarachnoid Hemorrhage in Rats - Li, Tong; Wang, Lingxiao; Hu, Quan; Liu, Song; Bai, Xuemei; Xie, Yunkai; Zhang, Tiantian; Bo, Shishi; Gao, Xiangqian; Wu, Shuhua; Li, Gang; Wang, Zhen (Frontiers in Neurology, 2017)
L-Cysteine is a semi-essential amino acid and substrate for cystathionine-β-synthase (CBS) in the central nervous system (CNS). We previously reported that NaHS, an H2S donor, significantly alleviated brain damage after subarachnoid hemorrhage (SAH) in rats. However, the potential therapeutic value of L-Cysteine and the molecular mechanism supporting these beneficial effects have not been determined. This study was designed to investigate whether L-Cysteine could attenuate early brain injury (EBI) following SAH and improve synaptic function by releasing endogenous H2S. Male Wistar rats were subjected to SAH induced by cisterna magna blood injection, and L-Cysteine was intracerebroventricularly administered 30 min after SAH induction. Treatment with L-Cysteine stimulated CBS activity in the prefrontal cortex (PFC) and H2S production. Moreover, L-Cysteine treatment significantly ameliorated brain edema, improved neurobehavioral function, and attenuated neuronal cell death in the PFC; these effects were associated with a decrease in the Bax/Bcl-2 ratio and the suppression of caspase-3 activation 48 h after SAH. Furthermore, L-Cysteine treatment activated the CREB-BDNF pathway and intensified synaptic density by regulating synapse proteins 48 h after SAH. Importantly, all the beneficial effects of L-Cysteine in SAH were abrogated by amino-oxyacetic acid (AOAA), a CBS inhibitor. Based on these findings, L-Cysteine may play a neuroprotective role in SAH by inhibiting cell apoptosis, up-regulating CREB-BDNF expression and promoting synaptic structure via the CBS/H2S pathway.